Global trends of the fast-food market in Kazakhstan - Balgabayeva, Z.B.; Medukhanova, L.A. (KU Publ., 2021)
Object: The purpose of the study is to analyze the main trends in the global fast-food market and outline the features and prospects of the local Kazakhstani fast-food market, taking into account the influence of the trend on a healthy lifestyle in this segment and its manifestation in Kazakhstan. Methods: The methodological basis of the research is a quantitative method of online questionnaires, analysis, generalization of data on changes in the fast-food market in new conditions, as well as comparison and extrapolation. Results: An overview of current global trends is presented and their manifestation in the Kazakhstani market is indicated. It is noted that the global trend for vegetable substitutes for meat products in the fast-food market currently does not have serious development in Kazakhstan, although elements of the flexitarian trend have already been manifested since healthy eating has taken a strong position in the behavioral characteristics and preferences of local consumers. There is a pronounced halal trend on the part of the Kazakh consumer, there is trust and national predisposition to it. The market leaders were identified by the number of points and the level of recognition. Conclusions: The study showed the concern of local consumers about the harmful component of the fast-food market, as well as a high percentage of respondents' doubts about the possibility of functioning of the fast-food industry in the field of healthy food in general (50 %). The prospects for the local fast-food market include the preconditions for the predominance of plant components, but not excluding natural meat, and on the contrary, even increased requirements for its environmental friendliness. Thus, in the Kazakhstani market, we can talk about the mixing of the global American and halal trends.
Қазақстандағы фастфуд нарығының ғаламдық тренді
Глобальные тренды рынка фастфуда в казахстане
Keywords: fast-food; halal; consumer preferences; global trends; healthy eating; problems of the fast-food market; flexitarianism